PENGARUH KUALITAS PRODUK, HARGA DAN MEDIA SOSIAL WA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK SKIN CARE PADA KLINIK DEVARI MEDIKA DI KABUPATEN PATI - Nanik Sugiarti; Fathorrahman .; Ike Kusdyah Rachmawati (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2023)
The purpose of this study was to determine and analyze: 1) the effect of product quality on purchasing decisions for skincare cosmetics at the Devari Medika Clinic in Pati Regency. 2). the effect of price on purchasing decisions for skincare cosmetics at the Devari Medika clinic in Pati Regency and 3). the influence of WA social media on the decision to purchase skincare cosmetics at the Devari Medika clinic in Pati Regency. This type of research is quantitative with a survey approach. This research was conducted on consumers who visited the Devari Medika Clinic in Pati Regency. The population in this study were consumers who visited the Devari Medika Clinic in Pati Regency. The sample was 100 people and the sampling was carried out using the Accidental Sampling technique for 1 month. The results showed 1) the quality of the product had an effect on purchasing decisions for skin care cosmetic products at the Devari Medika Clinic in Pati Regency, 2). WA prices and social media on purchasing decisions for skin care cosmetic products at the Devari Medika Clinic in Pati Regency and 3). social media on the decision to purchase skin care cosmetic products at the Devari Medika Clinic in Pati Regency.